2010
DOI: 10.1007/s10530-010-9830-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of an invasive plant (Mikania micrantha H.B.K.) by soils of three different forests in lower subtropical China

Abstract: Biological invasion represents one of the most serious threats to biodiversity, and invasion ecology research has become one of the central issues of contemporary environmental science. However, the relative role of soil development as correlated with succession in influencing variation in invasion resistance has seldom been examined. We hypothesized that the invasion potential of exotic plants depends on soil conditions. In this study, we explored variation among soils of three forest types in their resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 65 publications
2
19
1
Order By: Relevance
“…Resistance to alien plant invasion might result from the strong effects of a relatively small number of native species [32], such as in HF, CB, and MT [9]. Our results support a hypothesis of soil biotic resistance [33,34], and are congruent with a study by Hou et al [35], which showed MM was inhibited when exposed to soils from three different forests located in lower subtropical China.…”
Section: Soil Fungal Resistance To MMsupporting
confidence: 91%
“…Resistance to alien plant invasion might result from the strong effects of a relatively small number of native species [32], such as in HF, CB, and MT [9]. Our results support a hypothesis of soil biotic resistance [33,34], and are congruent with a study by Hou et al [35], which showed MM was inhibited when exposed to soils from three different forests located in lower subtropical China.…”
Section: Soil Fungal Resistance To MMsupporting
confidence: 91%
“…Some evidence has suggested that allelopathic native plants play a role in inhibiting the growth of invaders [37][38][39]. We found that the allelopathic activity in natural forest soil and litter inhibited the growth of P. americana but that RP soil promoted its growth (Figures 2 and 3), which seems to confirm our second hypothesis: Allelopathy of natural forests inhibits P. americana growth and that of the R. pseudoacacia plantation promotes its growth.…”
Section: The Effects Of Allelopathy On Plant Growthsupporting
confidence: 86%
“…Ning et al [37] provided evidence that in grassland communities allelopathic native grasses increased community resistance to introduced plants. However, this study did not produce results for succession-associated allelopathy consistent with Hou et al [39], who found that late-successional stage forest soils have stronger allelopathy than early-successional stages. Although litter leachate from F3 inhibited P. americana growth stronger than that of the other forests (Figure 3), the allelopathic effects of F3 and F4 soils on the growth of this plant were not significant ( Figure 2).…”
Section: The Effects Of Allelopathy On Plant Growthcontrasting
confidence: 66%
See 1 more Smart Citation
“…The original and expanded ranges of M. boisiana are quite near and there are no strong natural barriers as compared to that between China and America, and plants in the two ranges may have already preadapted to each other. Similarly, two recent studies found that allelopathy from some native plants in natural forests could inhibit the growth of exotic invasive M. micrantha that originated from South America [18], but did not inhibit the growth of M. boisiana [19]. Our results indicate that the mechanisms underlying the explosion of M. boisiana in the expanded range might not be due to its higher allelopathic effects as compared to non-expanding native congeneric species, although the weed does have allelopathic effects.…”
Section: Pot Culture Growth Bioassay Using a Naturally Co-occurring Pmentioning
confidence: 87%